Detailed genetic and clinical analysis of a novel de novo variant in HPRT1: Case report of a female patient from Saudi Arabia with Lesch–Nyhan syndrome - AlBakheet, Albandary; AlQudairy, Hanan; Alkhalifah, Joud; Almoaily, Sheikhah; Kaya, Namik; Rahbeeni, Zuhair (Frontiers in Genetics, 2023)
Background: Hypoxanthine-guanine phosphoribosyltransferase (HPRT1) deficiency is an inborn error of purine metabolism responsible for Lesch-Nyhan Syndrome (LNS). The disease is inherited in an X-linked recessive manner and predominantly effects males. Females can carry a mutation as heterozygotes but typically they are asymptomatic because of the random inactivation of affected allele. Nevertheless, although rarely, heterozygote females may manifest LNS with full characteristic. Herein, we describe a Saudi female with LNS. Results: The patient `(a 4-year-old girl) presented with typical characteristics of the disease, which includes global developmental delay, self-mutilation, hyperuricemia, hypotonia, speech delay, spasticity, and seizures. Her general biochemical laboratory results were normal except for high levels of uric acid. The abdominal MRI\MRS, mostly unremarkable, showed bilateral echogenic foci within the renal collecting system. Genetic testing (whole exome sequencing, iterative variant filtering, segregation analysis, Sanger sequencing) pointed a novel de novo frameshift variant in HPRT1. X-inactivation assay using HpaII showed presence of 100% skewed X chromosome carrying the affected allele. RT-PCR of cDNA indicated complete loss of the expression of the normal allele. Conclusion: Our study presents the 15th female patient, a severe case of LNS, from Saudi Arabia with 9th novel de novo variant of HPRT1, and briefly reviews previously reported female cases in the literature. The study emphasizes the need for a streamline protocol that will help for an early and accurate diagnosis of female LNS patients to avoid unnecessary interventions that lead to costly patient care.